English for Specific Purposes for Accounting Students at One of Vocational High Schools in Batanghari - Ismalinda, Siti (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2024)
This study aims to explore the perceptions of accounting students regarding the English textbooks used in accordance with the Merdeka Belajar Curriculum. The research employed a descriptive quantitative method, involving twenty-five accounting students. Data were collected using a Google Form questionnaire. The findings revealed that the twelfth-grade students agreed that the English textbook aligned well with their major. They noted that the material, vocabulary, grammar, reading passages, and speaking exercises were relevant to accounting. Furthermore, the exercises in the textbook were considered appropriate and in line with the Merdeka Belajar Curriculum, making the textbook highly suitable for accounting students.